2019
DOI: 10.15244/pjoes/94288
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Land Use Change of Sloping Farmland on Characteristic of Soil Erosion Resistance in Typical Karst Mountainous Areas of Southwestern China

Abstract: With the implementation of ecological projects such as the Grain-for-Green Project, rocky desertification control and comprehensive control of soil and water loss for sloping farmland, ecological environment of karst mountainous areas in southwest China has been improved significantly, but soil and water loss of sloping farmland is still an important ecological and environmental problem in this region. In this paper we took a typical karst rocky desertification mountainous area, Jinlan Demonstration Area, as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In Yunnan province, the average erosion modulus was 12.56 tha −1 a −1 , and more than 77% of areas above the middle erosion level were found in croplands (Duan et al, 2020). However, the conversion of sloping cropland to grassland and wasteland resulted in an increase in soil shear strength by 34.55% and 65.5%, respectively (Li et al, 2019). Besides, Tang et al (2020) predicted that the carbon storage loss caused by cropland reclamation in Hubei province would increase by 3.86 Tg during the period of 2010–2030.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Yunnan province, the average erosion modulus was 12.56 tha −1 a −1 , and more than 77% of areas above the middle erosion level were found in croplands (Duan et al, 2020). However, the conversion of sloping cropland to grassland and wasteland resulted in an increase in soil shear strength by 34.55% and 65.5%, respectively (Li et al, 2019). Besides, Tang et al (2020) predicted that the carbon storage loss caused by cropland reclamation in Hubei province would increase by 3.86 Tg during the period of 2010–2030.…”
Section: Discussionmentioning
confidence: 99%
“…Second, cropland reclamation in mountainous areas is an uneconomical practice because of the higher labor cost due to the fragmentation of the agricultural landscapes (Figure 9), which makes the large‐scale operation of agricultural machinery difficult and more labor input is required in the process of agricultural production compared to the plain areas (Zhu et al, 2018). For instance, Li and Li (2019) found that the agricultural labor productivity of maize in mountain areas was 2.25 times that in plain areas in 2013. In addition, according to the cost–benefit data of agricultural products, the labor cost of planting an acre of corn in the provinces of Yunnan and Guizhou is 2.24 times the national average in 2019 (National Bureau of Statistics, 2021a).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the prevention and control of soil and water loss during the early stages of construction are essential (Que & Zhang, 2021). At the same time, land‐use change has a significant impact on soil resistance to erosion in karst regions (Li, Wu, et al, 2019). Changing the land use from cropland to forest land or grassland, the soil erosion resistance increases (He et al, 2018; Li, Wu, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Knight et al [21] suggested that the addition of a grass zone to the outside of a riparian forest buffer would reduce sediment loss resulting from ephemeral gullies and increase stream water quality. Li et al [22] found an improvement in soil erosion resistance under the planting of grassy vegetation. Other BMPs, such as timing of cattle grazing, non-riparian shade, alternative water sources, and livestock exclusion with fencing, have been shown to effectively increase streambank stabilization [23,24], soil enzyme and microbial activities [25], and stream water integrity [14,26].…”
Section: Introductionmentioning
confidence: 99%